Celowość oparcia polskiego systemu nadzoru korporacyjnego na teorii corporate governance - Peszko, Adam (The Advisability of Basing the Polish Corporate Governance system on the Theories of Corporate Governance, 2006)
The resource dependency, stakeholder, agency, stewardship, institutional and managerial hegemony theories are presented in the first part of the study. The practical implication of these theories in the British-American and Euro-Japanese corporate governance models. The advisability to avoil the mentioned theories to improve the Polish corporate governance is also discussed system is discussed in the next parts of the study.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 369-381